The Content-Validated Geometry Lessons in Islam Observed Brain-based Learning - Sherma O. Sappari; Florante P. Ibarra; Amirul Mukminin; Kasinyo Harto; Lenny Marzulina; Herri Mulyono; Asmendri Asmendri (Qubahan Academic Journal)
This study examined the process of learning geometry in content-validated lessons with the integration of Islamic values as perceived to have observed brain-based learning principles. Anchored in a grounded theory, theoretical sampling was utilized among sixteen 4th and 5th grade students in geometry class including three teacher-observers and one teacher-demonstrator playing the “emic-etic” role or participant observer. Lessons in geometry with Islamic contexts were sporadically presented with citations of verses from the Holy Qur’an coupled with Islamic value-infusions. Designed in a qualitative grounded theory approach, an interview script was used for individual and focus group interviews.  Ten content validated -lessons in geometry were designed to capture the Islamized learning phenomenon wherein field notes of observations and video footages were qualitatively analyzed using the lens of systematic approach coined as constant comparative method of analysis. Results indicated that substantive theory on the process of learning geometry in content-validated lessons with Islamic value-infusions as perceived  to have brain-based learning was evidently observed which revolved on five sub-elements: (a) connection; (b) attention;(c) imagination and action; (d) emotions and recollection; and (e) associations. The approach to integrating Islamic values in content-validated lessons recognized the presence and the process of brain-based learning principles. Observed in cyclical context, emotion and memory play a significant role to learning guided by the content-validated lessons in geometry. The infusion of religious values and appreciation of creation informs one’s understanding of the emotions and their importance for learning which are therefore critical to brain-based learning principles.